2010
DOI: 10.1186/1472-6963-10-327
|View full text |Cite
|
Sign up to set email alerts
|

Can Fire and Rescue Services and the National Health Service work together to improve the safety and wellbeing of vulnerable older people? Design of a proof of concept study

Abstract: BackgroundOlder adults are at increased risk both of falling and of experiencing accidental domestic fire. In addition to advanced age, these adverse events share the risk factors of balance or mobility problems, cognitive impairment and socioeconomic deprivation. For both events, the consequences include significant injury and death, and considerable socioeconomic costs for the individual and informal carers, as well as for emergency services, health and social care agencies.Secondary prevention services for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 20 publications
0
42
2
Order By: Relevance
“…Unlike some other reports we did not find a significant correlation between living in a residential/nursing care facility and relative risk of death due to sustained burn injury as only 9 deaths (2.8%) occurred in these facilities [52]. Also in contrast to previous studies that have reported increasing mortality with increasing socioeconomic deprivation our study showed that within the GM region in the >75 years age group reducing deprivation increased the relative risk of death [54]. This regional variation has also been observed by the ONS in correlating accidental mortality with deprivation and can partly be explained by the relatively small number of deaths involved in comparison to chronic diseases such as ischemic heart disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike some other reports we did not find a significant correlation between living in a residential/nursing care facility and relative risk of death due to sustained burn injury as only 9 deaths (2.8%) occurred in these facilities [52]. Also in contrast to previous studies that have reported increasing mortality with increasing socioeconomic deprivation our study showed that within the GM region in the >75 years age group reducing deprivation increased the relative risk of death [54]. This regional variation has also been observed by the ONS in correlating accidental mortality with deprivation and can partly be explained by the relatively small number of deaths involved in comparison to chronic diseases such as ischemic heart disease.…”
Section: Discussioncontrasting
confidence: 99%
“…22 This program includes a fall prevention educational program provided by trained EMS providers but does not include a fall risk assessment. Also in the United Kingdom, a pilot study showed that linking older adults who had fallen and been seen by EMS but not transported to a hospital to a community-based fall prevention program reduced fall rates by 55%.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that emergency medical service (EMS) providers can engage and educate lay persons and affect practice for a number of important health conditions (7), and firefighters and emergency medical technicians (EMTs) are a well-trusted information source. However to-date, few studies have assessed the potential for an EMS role in fall prevention (8, 9), and data on the feasibility and effectiveness of proactive outreach by EMS providers in the context of a 9-1-1 call for a fall are lacking. Because of the widespread availability of EMS services throughout the United States, examination of an active EMS role in the prevention of falls is warranted.…”
Section: Introduction Background and Rationalementioning
confidence: 99%